Terpaan Lingkungan terhadap Kesetaraan Gender dalam Keluarga - Parwitaningsih Parwitaningsih; Hendrikus Ivoni Bambang Prasetyo; Nur Hayati; Sri Pujiati (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2023)
Gender socialization in the family is intended for children to learn about gender roles. It is the family that begins to teach a boy to adhere to masculine traits and a daughter to adhere to feminine traits. This gender learning process is often influenced by factors outside the family which then have an impact on gender equality. Therefore, research was conducted to examine how the environment influences the implementation of gender equality in the family. This study used a combined approach to collect and analyze quantitative and qualitative data because researchers wanted to see trends in data regarding the influence of the environment on gender equality in the family. The results of the study showed that the environment has a significant influence on the implementation of gender equality in the family. The higher the environmental exposure, the higher tendency of respondents not to implement gender equality. This means that there are still differences between boys and girls related to the type of task, type of toys, type of character, pride, and type of color. Every boy or girl already has their own references that have been determined by the family and influenced by the environment. The neighboring factor becomes the dominant factor, in which respondents are aware of these differences, compared to the mass media, friends, and parents. This implies that neighbors are a factor that has a significant influence on respondents in applying differentiation.